Artificial Vision Algorithms for Socially Assistive Robot Applications: A Review of the Literature - Victor Manuel Montaño-Serrano; Juan Manuel Jacinto-Villegas; Adriana Herlinda Vilchis-González; Otniel Portillo-Rodríguez (Sensors, 2021)
Today, computer vision algorithms are very important for different fields and applications, such as closed-circuit television security, health status monitoring, and recognizing a specific person or object and robotics. Regarding this topic, the present paper deals with a recent review of the literature on computer vision algorithms (recognition and tracking of faces, bodies, and objects) oriented towards socially assistive robot applications. The performance, frames per second (FPS) processing speed, and hardware implemented to run the algorithms are highlighted by comparing the available solutions. Moreover, this paper provides general information for researchers interested in knowing which vision algorithms are available, enabling them to select the one that is most suitable to include in their robotic system applications.